Gledališka pedagogika - Lešnik Jeras, Irina (Amfiteater (Ljubljana), 2023)
Theatre art can be included in education in different ways and with different goals. The first two pillars of theatre pedagogy – theatre literacy and theatre creation – have as their goal familiarisation with theatre art and theatre creation. The third pillar of theatre pedagogy – learning through theatrical approaches – understands theatre (or theatre approaches, methods and techniques) not only as a goal but primarily as a means for achieving broader educational goals. Drama in education (DiE) represents such a theatrical approach, which can be applied to various subject areas. In addition to educational goals, we also achieve aesthetic goals – we learn through drama and about drama. Drama in education belongs to the so-called process forms of drama, as it does not envisage a final product, that is, a performance. It originates from an improvised symbolic play/role play, and due to educational goals, it can also be argued that it indicates a learning approach in which the teacher/theatre pedagogue uses a combination of methods and techniques of theatre pedagogy connected in a meaningful dramatic structure. In addition to creative theatre activities, drama in education devotes most of its time to the negotiation and structuring of meanings directed by the teacher/theatre pedagogue. Even if a precise definition of drama in education is not possible, its key characteristics are processability, role play, improvisation, collectivity, dialogue and a symbolic dimension.
Keywords: drama in education; drama v izobraževanju; gledališka pedagogika; gledališki pristopi; igra vlog; improvisation; improvizacija; proces; process; role play; theatre approaches; theatre pedagogy; theatre studies